Encyclopedia of multimedia technology and networking - Pagani, Margherita, 1971- (Hershey PA : Idea Group Reference, 2005)
'This encyclopedia offers a comprehensive knowledge of multimedia information technology from an economic and technological perspective'--Provided by publisher
Includes bibliographical references and index
Keywords: Multimedia communications -- Encyclopedias